Extracorporeal Membrane Oxygenation use on Liver Transplantation: An Integrative Review - Zoby, Henrique Nóbrega; Falcão, Luísa Borges Oliveira de Arruda; Correia, Laura Cabral Barros; Rêgo, Marlon Vinicius Alves Soares; Wanderley, Giovanna Vasconcelos; Vilachan, Fernando Pires de Góes; Lima, Carlos Vinicius de Oliveira; Costa, Ludmila Rodrigues Oliveira; Silva, Hugo Rafael Souza e; Fonseca Neto, Olival Cirilo Lucena da (Brazilian Journal of Transplantation, 2023)
Objective: To review the applicability of extracorporeal membrane oxygenation (ECMO) during the pre, intra and postoperative periods of patients undergoing liver transplantation. Methods: This is an integrative review that seeks to evaluate the indications for the use of ECMO in liver transplantation. As databases, were used: MEDLINE, Web of Science and Scopus, with articles published in the last ten years in English and Portuguese. Results: In this review, 24 papers were included, of which 3 were original articles and 21 were case reports. The studies were divided according to the ECMO application period concerning the liver transplant: one for the preoperative, eight intraoperative and 15 postoperative. It was identified that ECMO use is mainly related to hepatopulmonary syndrome complications. The limited number of studies regarding using ECMO in the preoperative period reflects the importance of hepatic transplant as the main measure to manage liver disease complications. In the intraoperative phase, ECMO usage is expressive in managing cardiopulmonary complications refractory to previous interventions. The use of this mechanism in the postoperative period is the most reported. The main indication is severe hypoxemia secondary to hepatopulmonary syndrome, in which other treatments have been ineffective. The main complications related to this mechanism were sepsis, renal failure and bleeding. Conclusion: ECMO is an important therapeutic modality for managing complications resulting from liver transplantation. However, only some studies in the literature have an adequate sample number to assess its actual efficacy and level of safety.